Inequality and Inequity in Outpatient Care Utilization in Ethiopia: A Decomposition Analysis of Ethiopian National Health Accounts - Kifle H; Merga BT; Dessie Y; Demena M; Fekadu G; Negash B (Dove Medical Press, 2021)
Hilawi Kifle,1 Bedasa Taye Merga,2 Yadeta Dessie,2 Melake Demena,2 Gelana Fekadu,3 Belay Negash2 1Haramaya University Higher Health Center, Haramaya University, Haramaya, Ethiopia; 2School of Public Health, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, EthiopiaCorrespondence: Bedasa Taye MergaSchool of Public Health, College of Health and Medical Sciences, Haramaya University, P.O. Box 235, Harar, EthiopiaTel +251917723961Email tbadhaasaa@gmail.comBackground: Inequity in healthcare use is avoidable inequality, and it exists when there are differences in the use of healthcare after standardization of different needs among the population. In Ethiopia, wide variation and lower achievement exists in outpatient visit per person per year against the target to reach by 2020. Therefore, this study is aimed at measuring inequalities and inequities in outpatient care utilization in Ethiopia.Methods: The study utilized data from 2015/16 Ethiopian National Health Account survey. The analysis included a weighted sample of 42,460 individuals. Concentration curve and indices were used to measure inequality in outpatient care utilization. Deviations in the degree to which outpatient care was distributed according to need were measured by the horizontal inequity index. All statistical analyses were done using STATA version 14. In all analyses statistical significance was declared at a p-value < 0.05 and a 95% confidence interval.Results: The outpatient care utilizations were found to be concentrated among the rich. The actual (C = 0.0335, 95% CI: 0.0298, 0.0431) and need predicted (C = 0.0157, 95% CI: 0.0117, 0.0413) utilizations were concentrated among the rich. The distributions of outpatient care in Ethiopians were pro-rich (rich-favoring). The decomposition analysis revealed that need factors were the main positive contributors to the inequality (23.6%) and non-need factors were among the negative contributors to the inequality (− 48.4%).Conclusion: This study evidenced the presence of rich-favoring inequality and inequity in outpatient care utilization in Ethiopia. Therefore, there is a need to consider implementation strategies that focus on fairness in healthcare utilization.Keywords: national health accounts, outpatient care utilization, inequality, inequity, decomposition analysis, Ethiopia